Antidiabetic activity of blood burnet extract in high fructose fed rats - Klevanova, V.; Trzhetsynskiy, S. D.; Fedorovska, K.; Тржецинський, Сергій Дмитрович (Харків: Фармітек, 2015)
Insulin resistance is one of leading pathogenic process in diabetes mellitus type-2. It is known that highfructose intake leads to obesity, diabetes, dyslipidemia in rodents. Plants have been the primary source of drugs,and many of the currently available drugs have been directly or indirectly derived from plants. Aim. The aim of our study was to evaluate the effect of Blood burnet’s extract on body weight, visceral fat, blood glucose, plasma insulin, lipid pro.iles, lipid peroxidation and enzymatic antioxidants in fructose-induced type-2 diabetic rats.